Response of fenugreek (Trigonella foenum-graecum) to bio-regulators TGA and N-acetyl cystein under drip irrigation levels - M Arif, S R Bhunia, I M Verma, (Journal of Spices and Aromatic Crops, 2017)
Field experiments were conducted during winter seasons of 2010–11 and 2011–12 at Bikaner (Rajasthan) to study the effect of bioregulators viz., TGA and N-acetyl cystein under different drip irrigation levels on yield, yield attributes, water use and water use efficiency of fenugreek. The highest plant height (69 cm) and yield attributes viz., branches plant-1 (7.6), pods plant-1 (46.3), pod length (13.5 cm), seed pod-1 (16) and test weight (12.7 g) were recorded with 100% ETc + TGA (200 ppm). Further, 80% ETc + TGA (200 ppm), and 100% ETc + N-acetyl cystein (both 10 and 20 ppm) and 100% ETc + TGA (both 100 and 200 ppm) produced comparable plant height. However, 80% ETc + N-acetyl cystein (both 10 and 20 ppm), 80% ETc + TGA (both 100 and 200 ppm), 100% ETc + N-acetyl cystein (both 10 and 20 ppm), 100% ETc + TGA (100 ppm) and 100% ETc + TGA (200 ppm) recorded at par branches plant-1, pods plant-1, pod length and test weight of fenugreek. Highest seed and biological yield of fenugreek were recorded with 100% ETc + Nacetyl cystein (20 ppm), which was at par with 100% ETc + N-acetyl cystein (10 ppm) and 100% ETc + TGA (both 100 and 200 ppm). Maximum water use recorded at 100% ETc with or without bioregulators, whereas maximum water use efficiency was recorded with 60% ETc + N-acetyl cystein (20 ppm) followed by 60% ETc + N-acetyl cystein (10 ppm).